Operadores de Calderón-Zygmund e o Teorema T(1) - Silva, Pedro Henrique Takemura Feitosa da (2021)
The purpose of this work is to present, in a detailed way, one of the main topics of Harmonic Analysis: the singular integral operators or, in its general form, the Calderón-Zygmund operators. We did here, for the most part, a literature review of [GFK1] e [GFK2], aprocching necessary concepts to prove the so known T(1) Theorem, which was first proved by G. David and J-L. Journé in the article [D-J], which characterizes the L^2 boundedness of a certain class of operators. This text may be accessible for anyone who has basic notions in Measure Theory and Functional Analysis, for instance see [BSS], [FLD], [CNW] AND [BZS].